(untitled) (Bangladesh Journal of Medical Microbiology, 2020)
Background and objectives: Carbapenem resistance is an emerging problem worldwide. Detection of carbapenem resistance genes is important to institute appropriate therapy and to initiate preventive measures. This study was conducted to determine the presence of carbapenemase enzyme producing Escherichia coli and Klebsiella species in a tertiary care hospital of Bangladesh, as well as to observe the patterns of antibiotic resistance and carbapenem resistance genes among them. Methodology: Total 166 Escherichia coli, Klebsiella pneumoniae and Klebsiella oxytoca were isolated from urine, wound swab, pus, sputum and blood samples of patients of Dhaka Medical College Hospital. Antibiotic susceptibility test was performed by disk-diffusion technique. Carbapenemase producers were detected phenotypically by Double-disk synergy (DDS) test, Modified Hodge test (MHT) and Combined disk (CD) assay. Minimum inhibitory concentration (MIC) of imipenem was done by agar dilution method among carbapenemase producing strains. Genotypically carbapenemase genes (blaNDM-1, blaVIM, blaIMP, blaKPC, blaOXA-48/blaOXA-181) among the imipenem resistant Escherichia coli and Klebsiella species were detected by polymerase chain reaction (PCR). Sequencing was done to differentiate blaOXA-181 gene from blaOXA-48 gene. Class 1 integron were also detected by PCR using specific primer among carbapenemase producers. Results: Thirty seven (22.29%) imipenem resistant isolates were detected during disk-diffusion technique, among them 16 (43.24%) carbapenemase producers were detected by MHT, 20 (54.05%) by DDS test, 22 (59.46%) by CD assay and 23 (62.16%) by PCR. Out of 23 carbapenemase producing strains, MIC of imipenem ranged from 4 μg/ml up to ≥128 μg/ml. NDM-1 (43.24%) was the dominant genotype in imipenem resistant strains followed by KPC (21.62%) and OXA-181 (18.92%). Class 1 integron were present in 16 (69.57%) of the genotypically identified carbapenemase producers. Conclusion: The results of this study showed high proportion of carbapenemase enzyme producing Escherichia coli and Klebsiella species in Bangladesh. Genes encoding carbapenemase enzymes including blaNDM-1, blaKPC, blaVIM, blaIMP and blaOXA-181 were responsible for imipenem resistance. blaNDM-1 producers are increasing and blaKPC and blaOXA-181 producers are emerging in Bangladesh. Regular surveillance of antibiotic resistance should be done in every tertiary care hospital to prevent spread of these strains. Bangladesh J Med Microbiol 2020; 14 (2): 25-29